Design of 2D Animation Character Concept Art as a Promotional Medium for the Dewi Sartika Museum and Bandung Good Guide - Rahmi, Lutfia Fatihah; Isa Pramana Koesoemadinata, Mohammad; Belasunda, Riksa; Swasty, Wirania (International Journal Labs, 2026)
Dewi Sartika is an Indonesian education pioneer who fought for women’s right to education in the early 20th century. However, her values are gradually being forgotten, even at SD–SMP Dewi Sartika Bandung, which carries her educational legacy. The institution faces challenges such as weak identity, limited promotion, and low appeal to young audiences and tourists. This study focuses on designing 2D character concept art as part of a digital promotional strategy for the Living Museum Sakola Kaoetamaan Istri, in collaboration with Bandung Good Guide. The characters are designed as local tourists joining cultural walking tours, serving as visual representations that connect Dewi Sartika’s educational heritage with Bandung’s creative tourism. with design thinking approach, the research applies the empathize and define stages to understand audience behavior, and the ideate and prototype stages to visualize character designs using user persona–based character design approach within the framework of participatory design for character design. The results show that character-based storytelling supported by Bandung Good Guide’s media network is more effective than conventional methods in attracting young audiences and cultural tourists. This approach helps revitalize historical values while strengthening the museum’s role as a cultural heritage destination in Bandung.